Oral vs Intravenous Antibiotics for Patients With Klebsiella pneumoniae Liver Abscess: A Randomized, Controlled Noninferiority Study. (23rd October 2019) - Molton, James S; Chan, Monica; Kalimuddin, Shirin; Oon, Jolene; Young, Barnaby E; Low, Jenny G; Salada, Brenda M A; Lee, Tau Hong; Wijaya, Limin; Fisher, Dale A; Izharuddin, Ezlyn; Koh, Tse Hsien; et al.
Abstract: Background: Klebsiella pneumoniae liver abscess (KLA) is emerging worldwide due to hypermucoviscous strains with a propensity for metastatic infection. Treatment includes drainage and prolonged intravenous antibiotics. We aimed to determine whether oral antibiotics were noninferior to continued intravenous antibiotics for KLA . Methods: This noninferiority, parallel group, randomized, clinical trial recruited hospitalized adults with liver abscess and K. pneumoniae isolated from blood or abscess fluid who had received ≤7 days of effective antibiotics at 3 sites in Singapore. Patients were randomized 1:1 to oral (ciprofloxacin) or intravenous (ceftriaxone) antibiotics for 28 days. If day 28 clinical response criteria were not met, further oral antibiotics were prescribed until clinical response was met. The primary endpoint was clinical cure assessed at week 12 and included a composite of absence of fever in the preceding week, C-reactive protein <20 mg/L, and reduction in abscess size. A noninferiority margin of 12% was used. Results: Between November 2013 and October 2017, 152 patients (mean age, 58.7 years; 25.7% women) were recruited, following a median 5 days of effective intravenous antibiotics. A total of 106 (69.7%) underwent abscess drainage; 71/74 (95.9%) randomized to oral antibiotics met the primary endpoint compared with 72/78 (92.3%) randomized to intravenous antibiotics (risk difference, 3.6%; 2-sided 95% confidence interval, −4.9% to 12.8%). Effects were consistent in the per-protocol population. Nonfatal serious adverse events occurred in 12/72 (16.7%) in the oral group and 13/77 (16.9%) in the intravenous group. Conclusions: Oral antibiotics were noninferior to intravenous antibiotics for the early treatment of KLA. Clinical Trials Registration: NCT01723150. Abstract : In this randomized noninferiority trial of 152 patients with Klebsiella pneumoniae liver abscess, the proportion criteria for clinical cure with early oral antibiotics compared with intravenous antibiotics was 95.9% vs. 92.3%, which was within the noninferiority margin of 12%.